Managerial Ability and Foreign Ownership: Mechanisms for Increasing Firm Value - Paulus Tangke (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
The purpose of this study is to investigate the effect of managerial ability and foreign ownership on the quality of financial reporting, investigate the effect of managerial ability, foreign ownership and quality of financial reporting on firm value, and investigate the effect of managerial ability and foreign ownership on firm value mediated by the quality of financial reporting. This type of research is an explanatory research (explanatory research) and the main theory used in this study is the Stakeholder Theory and there is also a supporting theory used in this research, namely Agency Theory. Population used is the whole company public listed in Indonesia Stock Exchange period 2016-2018. Number of samples are 270 firms each year, was selected by purposive sampling method and using secondary data, i.e. the annual report and financial statements. The analytical method used is path analysis and hypothesis mediation analysed by using Sobel test. The results of this research show that managerial ability has a negatiive and significant impact on financial reporting quality and foreign ownership has a positive and not significant on financial reporting quality. Managerial ability has a positive but not significant effect on firm value and foreign ownership has a positive and significant effect on firm value, and financial reporting quality has a positive but not insignificant effect on firm value. This study also shows that the quality of financial reporting does not play a role in mediating managerial ability and foreign ownership of firm value.